Fatores de vulnerabilidade financeira das universidades federais brasileiras - Galdino, Marlon Coqueiro (2020)
Federal universities are institutions that enjoy financial autonomy and administrative autonomy and aprreciate quality education and free education. However, studies show that financial autonomy has never been achieved, because to factors that can affect their budgets, making them vulnerable. In order to identify the variables that are associated with the vulnerability of Brazilian federal universities, this work arises. From this general objective, the specific objectives are born: (i) to identify the endogenous and exogenous variables that make up the vulnerability of universities; (ii) to verify the division of the university budget among the spending groups (iii) to detect evidence of the occurrence of the political cycles of the presidential elections at federal universities. For theoretical basis, the main literature used was the Theory of Political Cycles in order to understand whether there is an association of electoral variables in the vulnerability of entities. To achieve the general objective and specific objectives, it was established that the universe of research would be the 63 universities created before 2018, with a time period comprising 2008 to 2018, totalizing 648 observations. The data were organized in a panel to combine year with the institution. For the analysis and treatment of the data, descriptive statistics resources were used, and econometric models such as Multiple Logistic Regression. Three research hypotheses were established. The first refers to the association between the variation of investment expenditures and vulnerability and the second is the existence of the influence of Political Cycles on the vulnerability of entities, in which both hypotheses were corroborated after the test. Finally, it was defined that the political cycles present in the association of variables can be both the Classic Opportunist Model and the Classic Party Model.